Combining Proteomics and Metabolomics to Analyze the Effects of Spaceflight on Rice Progeny - Zeng, Deyong; Cui, Jie; Yin, Yishu; Dai, Cuihong; Zhao, Haitian; Song, Chen; Guan, Shuanghong; Cheng, Dayou; Sun, Yeqing; Lu, Weihong (Frontiers in Plant Science, 2022)
Spaceflight is a special abiotic stress, the biological effect mechanism of which on contemporary rice has been clarified, but its effect on offspring rice was still unclear. In order to understand the response mechanism of F2 generation plants to space flight, this study used SJ-10 recoverable satellite to carry DN423 rice seeds for 12.5 days in orbit flight. After returning to the ground, the plants were planted to F2 generation to explore the biological effect mechanism. Our research showed that in the F2 generation of TLS, the rice plant height of the space flight group increased by 33.8%, the ear length and thousand-grain weight decreased by 9.7% and 4.6%, respectively, and the grain number per panicle increased by 6.5%. Moreover, related proteins that control changes in agronomic traits have been identified. The changes of MDA, H2O2, soluble sugar, electron leakage and antioxidant enzyme activity confirmed the stress response in F2 generation plants. Using iTRAQ and LC-MS technology to reveal the change pattern of protein levels and metabolite levels in F2 generation plants, 389 and 405 proteins were identified as differentially expressed in TLS and TS, respectively. In addition, there were 124 and 125 metabolites that changed during these two periods. The proteome and metabolome result further confirmed that the F2 generation plants still retained the memory of space flight stress, and retained the memory of space flight stress through genome instability. Oxidative stress signals activated sugar signals to rebuild metabolic networks to adapt to space flight stress. The reconstruction of energy metabolism, amino acid metabolism, phenylalanine metabolism, and flavonoid metabolism played an important role in the process of adapting to space flight stress. The results of this study broaden the perspective of space biological effects and provide a basis for studying the effects of abiotic stress on plant progeny.